RNAi of AGAMOUS genes in sweetgum alters reproductive organ identity and decreases fruit persistence. (21st May 2020) - Klocko, Amy L.; Brunner, Amy M.; Ma, Cathleen; Etherington, Elizabeth; Rosenstiel, Kori; Magnuson, Anna; Taylor, Barbara J.; Cappellazzi, Jed; Lockwood, Thomas; Covarrubias, Nichole; Bao, Manzhu; Morrell, Jeffrey J.; et al.
Abstract: Sweetgums ( Liquidambar ), members of the family Altingiaceae (Altingiales), have inflorescences and floral organs that are distinctive in structure compared with other angiosperms in which the roles of floral homeotic genes have been studied. To begin to understand the role of AGAMOUS (AG)—a floral homeotic gene that has a major role in stamen and carpel development—in development of the monosexual flowers of sweetgum, we used RNAi to reduce the expression of two members of the AG subfamily. Because AG suppression should induce floral sterility, RNAi might also provide a tool to mitigate the risks of invasiveness—and to reduce the production of its nuisance fruits or allergenic pollen—when sweetgum is used as an exotic shade or forest tree. We tested 33 independent transgenic events and non‐transgenic controls during 10 years in the field. The RNAi‐ AG sweetgum trees maintained normal growth, phenology, and vivid fall coloration during the 10 years of study, but 8 insertion events had highly modified inflorescence and floral morphology. The modified flowers had anthers and carpels that were converted to flat leaf‐like structures lacking pollen grains and ovules, respectively. The female inflorescences developed into dry papery structures that failed to produce seeds. These infructescences were smaller than control infructescences, and lost a greater percentage of biomass in a controlled decay assay. RNAi against AG genes was highly effective at impairing fertility and modifying reproductive development without significant vegetative effects in sweetgum and gave phenotypes distinct from, but similar to, that of AG loss of function in other angiosperms.